2008
DOI: 10.1042/cs20070444
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of air pollution

Abstract: Air pollution is a heterogeneous mixture of gases, liquids and PM (particulate matter). In the modern urban world, PM is principally derived from fossil fuel combustion with individual constituents varying in size from a few nanometres to 10 microm in diameter. In addition to the ambient concentration, the pollution source and chemical composition may play roles in determining the biological toxicity and subsequent health effects. Nevertheless, studies from across the world have consistently shown that both sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
395
0
15

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(436 citation statements)
references
References 134 publications
(213 reference statements)
5
395
0
15
Order By: Relevance
“…In recent years, researchers are finding it worthy to investigate potential links between PM 2.5 exposure and adverse birth outcomes (Slama et al, 2008;Dadvand et al, 2013), epigenetic alteration (Baccarelli et al, 2008;Salam et al, 2012;Byun et al, 2013;Hou et al, 2013) infant mortality (Woodruff et al, 1997;Lipfert et al, 2000;Dales et al, 2004;Glinianaia et al, 2004) atherosclerosis (Araujo et al, 2008;Araujo, 2011;Kaufman, 2011), stroke (Brook, 2008;Brook andRajagopalan, 2009, 2012;Maheswaran et al, 2010Maheswaran et al, , 2012, rheumatic autoimmune disease (Zeft et Table 1. Particulate matter and health outcomes for PM 10 , PM 2.5 and ultrafine particles (UFPs).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers are finding it worthy to investigate potential links between PM 2.5 exposure and adverse birth outcomes (Slama et al, 2008;Dadvand et al, 2013), epigenetic alteration (Baccarelli et al, 2008;Salam et al, 2012;Byun et al, 2013;Hou et al, 2013) infant mortality (Woodruff et al, 1997;Lipfert et al, 2000;Dales et al, 2004;Glinianaia et al, 2004) atherosclerosis (Araujo et al, 2008;Araujo, 2011;Kaufman, 2011), stroke (Brook, 2008;Brook andRajagopalan, 2009, 2012;Maheswaran et al, 2010Maheswaran et al, , 2012, rheumatic autoimmune disease (Zeft et Table 1. Particulate matter and health outcomes for PM 10 , PM 2.5 and ultrafine particles (UFPs).…”
Section: Introductionmentioning
confidence: 99%
“…Soluble transition metals and organic molecules adsorbed on to the surface of particles are capable of generating reactive oxygen intermediates in lung cells and activating redox-sensitive transcription factors to enhance inflammatory reactions [27]. Moreover, soluble constituents of PM 2.5 that can cross the pulmonary epithelium into the circulation may directly affect the cardiovascular system via imbalance of the autonomic nervous system, systemic oxidative stress, and inflammatory response [28].…”
Section: Discussionmentioning
confidence: 99%
“…The Harvard Six Cities study showed that the cardiopulmonary mortality was increased up to 37% in the population exposed to high levels of ambient PM 2.5 over a period of 14–16 years 22. The analysis from a population of 50 million living in the major U.S. cities (The National Morbidity, Mortality and Air Pollution Study) indicated that an increase of 10 μg/m 3 in PM 10 was related to an increase in 0.68% in cardiopulmonary mortality 23, 24, 25. Every 10 μg/m 3 increase in PM 2.5 exposure was also associated with an increase in 4.5% in coronary artery disease (CAD) 26.…”
Section: Pm and Cardiovascular Diseasesmentioning
confidence: 99%